The different functions of norrin - Braunger, Barbara M.; Tamm, Ernst R. (Advances in Experimental Medicine and Biology, 2012)
Norrin is a secreted protein which is encoded by the NDP gene mutated in Norrie disease. In the eye, the major site of Norrin expression is the Müller glia. Norrin activates the canonical Wnt/β-catenin signaling pathway via specific binding to the frizzled (Fzd)4/low-density lipoprotein receptor-related protein (Lrp)5/6 receptor complex, and is part of an essential signaling system that controls the formation of retinal capillaries during development. Independent from its angiogenic function, Norrin has pronounced neuroprotective properties on retinal ganglion cells via activation of Wnt/β-Catenin signaling and subsequent induction of neurotrophic growth factors in Müller cells. In addition, there is evidence that the expression of Norrin in uterus and placenta is required for reproduction © 2012 Springer Science+Business Media, LLC.
CRIS-Team Scopus Importer:2023-04-11
Keywords: Angiogenesis; Frizzled 4; Neuroprotection; Norrie Disease; Norrin; Retinopathy Of Prematurity; Transgenic Mice; Wnt/β-Catenin Signaling